CHARACTERISTICS OF SEDIMENT DISTRIBUTION AND PROSPECTS OF MARINE PLACERS IN SHALLOW COASTAL WATERS OF BINH DINH PROVINCE - Hieu, Trinh The; Dan, Nguyen Dinh (Vietnam Journal of Marine Science and Technology, 2019)
This paper presents characteristics of distribution of sediment types in shallow coastal waters (0–50 m water) in Binh Dinh province. The results show that sediments of the surface layer of the studied area have a rather complicated distribution, reflecting many sedimentation periods, in which the sandy sediment type is predominant. They consist of eight types of sediment and are divided into five major zones of sediment from the shore to the corresponding depths: From shore to 5 m, 6–24 m, 31–33 m, 35–47 m, and from 47 m or more. The paper also outlines the heavy mineral prospects contained in the sediments, including: Ilmenite, rutile, zircon, anatase, monazite, magnetite. Heavy minerals are concentrated mainly in the grain size from 0.125–0.25 mm, among which ilmenite is predominant with content in the heavy range of 65.5–83.43% and is mainly distributed in the type of fine sand deposits at depths from 5 m to 24 m. Based on that, it is possible to delineate five prospective areas within the study area